2018
DOI: 10.1186/s12936-018-2492-1
|View full text |Cite
|
Sign up to set email alerts
|

Malaria parasitaemia, anaemia and malnutrition in children less than 15 years residing in different altitudes along the slope of Mount Cameroon: prevalence, intensity and risk factors

Abstract: BackgroundMalaria, anaemia and malnutrition are frequently co-existing diseases that cause significant morbidity and mortality particularly among children. This study measured the prevalence, intensity and evaluated risk factors for malaria parasitaemia, anaemia and malnutrition among children living at low versus high altitude settings in the Mount Cameroon area.MethodsA cross-sectional community based survey involving 828 children aged 6 months to 14 years was conducted between July and November 2017. Malari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
52
4
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 34 publications
23
52
4
3
Order By: Relevance
“…In the present study, only approximately one-third of schoolchildren reported sleeping under mosquito nets during the malaria transmission season, with no signi cant association with reduced malaria prevalence. This nding is consistent with those reported for Ugandan and Cameroonian children [34,51] but inconsistent with that reported among Malawian schoolchildren [36]. The low utilisation of mosquito nets among schoolchildren is in agreement with that (19.0%) reported at the community level in Hodeidah in 2016 [52].…”
Section: Sociodemographic and Risk Factors Associated With Falciparumsupporting
confidence: 72%
“…In the present study, only approximately one-third of schoolchildren reported sleeping under mosquito nets during the malaria transmission season, with no signi cant association with reduced malaria prevalence. This nding is consistent with those reported for Ugandan and Cameroonian children [34,51] but inconsistent with that reported among Malawian schoolchildren [36]. The low utilisation of mosquito nets among schoolchildren is in agreement with that (19.0%) reported at the community level in Hodeidah in 2016 [52].…”
Section: Sociodemographic and Risk Factors Associated With Falciparumsupporting
confidence: 72%
“…In the present study, only approximately one-third of schoolchildren reported sleeping under mosquito nets during the malaria transmission season, with no signi cant association with reduced malaria prevalence. This nding is consistent with those reported for Ugandan and Cameroonian children [34,50] but inconsistent with that reported among Malawian schoolchildren [36]. The low utilisation of mosquito nets among schoolchildren is in agreement with that (19.0%) reported at the community level in Hodeidah in 2016 [51].…”
Section: Sociodemographic and Risk Factors Associated With Falciparumsupporting
confidence: 72%
“…Batoke-Limbe is situated at the foot of Mount Cameroon and is bounded to the west by the Atlantic Ocean. The area has been described in detailed by Teh et al [23].…”
Section: Study Area and Participantsmentioning
confidence: 99%
“…This reveals that malaria remains a major cause of illness during childhood and the prevalence in this part of the country is not on a speedy decline. In addition, Batoke is at a lower altitude and several studies have reported that malaria prevalence is higher in lower altitude compared to their higher altitude counterparts [23,24].…”
Section: Malaria Parasite Itn Knowledge and Haematological Indicesmentioning
confidence: 99%